The impact of local government characteristics on the accomplishment of Sustainable Development Goals (SDGs) - Nafila Dwi Mutiarani; Dodik Siswantoro (Cogent Business & Management, 2020)
The research aims to analyze the impact of local government's characteristic on the accomplishment of Sustainable Development Goals (SDGs) in Indonesia. The United Nations's Sustainable Development Goals (SDGs) represent a global action plan, approved by world leaders, intended to put an end to poverty, diminish social discrepancies, and protect the environment. The SDGs consist of 17 objectives and 169 targets that are scheduled to be achieved by 2030. Indonesia began to implement these SDGs in 2015. This present study involves 34 provinces as samples with the observation period being 2015-2016. Multiple regression analysis is used here for testing the research hypothesis which is in relation to the scoring of the accomplishment of the Sustainable Development Goals within the provinces studied. The results obtained by this study represent the characteristics of local government in terms of region size, the number of the regional work units, and the existence of local own-source revenue, impacting the accomplishment of the SDGs. The implication of this research is that local government needs a great effort and resource to fulfill the SDGs. This must be supported by a strong leader of local government and good infrastructure as well as the system.
Keywords: 650; sustainable; government; size; unit; revenue